Environmental aspects for use of municipal wastewater mud in phytoenergy - Gritsulyak , G.M.; Lopushnyak, V.I. (AgroChemistry and Soil Science, 2016)
The results of studies of heavy metals in the profile of soddy-podzolic soil of Precarpathians by application, in terms of 3-year field experiment, wastewater mud as fertilizer for willow energy are presented. It is found that this measure contributes to the content of heavy metals, particularly cobalt and nickel - in eluvial horizon (E), and lead and cadmium - in the humus-eluvial (НЕ), and causes a significant increase of heavy metals content in vegetative mass of willow within maximum concentration limit. Most of the absorbed pollutants are kept by plants in their underground part. The use of sludge as compost with sawdust or straw is effective way to enhance the safety of their use as causing significantly less accumulation of heavy metals in soil and vegetative mass of willows under the same application rate.